Effect of thermal cycles on the engineering properties and durability of sustainable fibrous high-strength concrete - Hakeem, Ibrahim Y.; Hosen, MD. Akter; Alyami, Mana; Qaidi, Shaker; Özkılıç, Yasin O.; Alhamami, Ali; Alharthai, Mohammad (Frontiers in Materials, 2023)
In this research, the effect of heat-cool cycles (HCC) was studied on high-strength concrete (HSC) containing steel fibres (SF), polypropylene fibres (PPF), and date palm fibres (DPF), which were named fibrous high-strength concrete (FHSC). To produce FHSC, three doses of 0.2, 0.6, and 1 percent of each fibre were utilized. All samples were tested after 28-days of normal water curing and 270-days of exposure to HCC (continuing the authors' project and research published at 28- and 180-days). This entails heating for 2-days at 60 oC in the oven and cooling for another 2-days at room temperature for 270-days. The experiment's findings revealed that fibre reinforcement in concrete enhances its strength and durability. By incorporating the three types of fibres into high-strength concrete, with-and-without HCC, the modulus of rupture was significantly increased. In both conditions, including with-or-without the implementation of HCC, incorporating the three fibre types into the HSC showed a significant increase in toughness. As a result, natural date palm fibres can produce sustainable FHSC that can withstand harsh environmental conditions. Moreover, compared to the previous study conducted by the authors at 180-days, there is a slight severity in both the pattern of decrease and increase of the studied characteristics at 270-days caused by the effect of thermal cycles and fibres.